1991
DOI: 10.1128/jb.173.17.5507-5515.1991
|View full text |Cite
|
Sign up to set email alerts
|

Altered phosphorylation of Bacillus subtilis DegU caused by single amino acid changes in DegS

Abstract: The Bacillus subtilis sacU locus consists of the degS and degU genes, which play a major role in controlling the production of degradative enzymes including extraceilular proteases. DegS has been shown to be autophosphorylated and to transfer the phosphoryl group to DegU. In this study, we partially purified the DegS proteins which carry amino acid changes resulting from various mutations and examined the phosphorylation reaction. The mutations used were degS42, causing a reduction in exoprotease production, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…We therefore investigated whether the suppression of degR expression by pLC1 also requires DegS. Strain ODM601 is isogenic to strain ODM50 except that it carries the degS42 mutation, a mutation that causes deficiency in autophosphorylation of DegS and subsequent phosphorylation of DegU (27). Results showed that pLC1 had no inhibitory effect on the transcription of degR in the degS42 background (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore investigated whether the suppression of degR expression by pLC1 also requires DegS. Strain ODM601 is isogenic to strain ODM50 except that it carries the degS42 mutation, a mutation that causes deficiency in autophosphorylation of DegS and subsequent phosphorylation of DegU (27). Results showed that pLC1 had no inhibitory effect on the transcription of degR in the degS42 background (Fig.…”
Section: Figmentioning
confidence: 99%
“…In the essential degS-degU system, the sensor kinase, DegS, is thought to accept certain environmental stimuli, autophosphorylate on its own histidine residue, and transfer the phosphate to the aspartate residue of the cognate response regulator DegU (2,17,18,24). DegS is also involved in the dephosphorylation of the phosphorylated DegU (3,27). In the regulation of the exoprotease production, other regulatory factors including DegR (19,20,28,31) and ProB (21) act in concert with the DegS-DegU system.…”
mentioning
confidence: 99%
“…DegS is also involved in the dephosphorylation of the phosphorylated DegU (6,28). It has been demonstrated that the phosphorylated form of DegU is stabilized by multiple copies of degR (29) or mutations that cause overproduction of the exoproteases, such as degSlOO(Hy), degS200(Hy), degU32(Hy), and degU9(Hy) (6,7,41,43).…”
mentioning
confidence: 99%
“…DegS is a cytoplasmic bifunctional protein that exhibits kinase and phosphatase activities (Tanaka et al, 1991). DegS interacts with the SMC-ScpA-ScpB complex, which controls DNA condensation and repair.…”
Section: Degu Phosphorylationmentioning
confidence: 99%